Resolutions regarding the Beveridge Report
1943-02-22 1943 1940s 2 pages Farnsworth Avenue, Rainworth, Mansfield, Notts. Feb. 22. 1943. Dear Sir, At a specially convened meeting of the Rainworth branch of the National Union of Agricultural Workers held on Monday, Feb.22.1943, the following resolutions were adopted unanimously by those present:- 1. That the Beveridge Report is a scheme designed as a concession to the workers in order to stave off social revolution. 2. That as it nevertheless provides a measure, however INADEQUATE of economic security at PRESENT almost completely lacking, its passing into law at an early date would result in a desirable amelioration of the living conditions of the workers. 3. That the obstructive attitude of the Government and the majority of Conservative Members of Parliament towards the Report provides further proof of the insincerity of the Government's vague promises of social improvement for after the war. 4. That the Chamber of Commons, as at present constituted, elected long before the war on a policy of loyalty to the League of Nations, subsequently deserted, does not remotely reflect the state of public opinion in the country today. 5. That it is therefore the duty of the Trade Unions, and of the Labour Movement as a whole, to press for a General Election, to take place within a comparatively short time. 6. That, should the Government refuse to permit a General Election, the Trade Unions and the Labour Movement should call upon the Labour Members of the Government either to resign from office or to leave the Party, and should consult on measures of concerted action by which the workers can ensure that the Government accedes to the demand for an early General Election. P.T.O. 292/150.5/5/145